Self Efficacy Of Mother Working In Giving Mother Milk Water With Baby Growth - Prihatini, Monika Sawitri; Probowati, Ririn; Ratnawati, Mamik (Universitas STRADA Indonesia, 2019)
Background: The paradigm change that there is no difference between men and women demands equal rights between women and men. Many mothers work as career women, so many women replace breastfeeding with formula milk. Based on government regulations No. 33 of 2012, a mother is obliged to give exclusive breastfeeding to her baby.Purpose: This study aims to determine the relationship between self efficacy of working mothers in breastfeeding and infant growth.Method: The type of correlational analytic research is cross sectional approach. The population and sample of working mothers who have babies aged 0-6 months on May 9 to June 6, 2018 at PT Mufasufu Sejati Jaya Lestari MPS Ploso are 30 respondents with a total sampling technique. Independent variable Self Efficacy for working mothers in breastfeeding, dependent variable for infant growth. The growth instrument uses a standard table of body weight/body length from the Ministry of Health and a Self Efficacy questionnaire for mothers to provide breastfeeding. Data analysis using chi square.ResultsThe results of the Chi-Square test analysis at the significance level of ? = 0.05 found that ? <? or 0.048 <0.05, there is a relationship between self-efficacy of mothers working in breastfeeding and growth in infants.Conclusion: The head of the agency/company must provide nursing mothers with exclusive breastfeeding by providing a lactation corner so that the mother can milk the milk and store it in the freezer in the refrigerator and take it home to give to the baby while the mother is working so that the baby continues to get milk without formula milk